Remediation of amoxicillin-contaminated water using zeolite from coal bottom ash - Galuh Yuliani; Nedya Tresna Dwi Hidayah; Maryono Maryono; Budiman Anwar; Mamun Mollah; Jessica Veronica; Agus Setiabudi (Universitas Sebelas Maret, 2025)
The contamination of antibiotics in water bodies has increased significantly in recent years. Various treatments, including adsorption, have been sought, but most include expensive sorbent material with low efficiency. This research reported an alternative sorbent material; synthetic zeolite derived from coal-burning waste. Coal bottom ash was converted to zeolite via a hydrothermal technique using various concentrations of NaOH and relatively low-temperature conditions. X-ray diffractogram confirms the formation of ZSM-23 when a 1:2 coal-to-zeolite ratio was used at 95°C. The FTIR spectra also highlighted the characteristics of zeolite functional groups, such as the Si−O vibration at 999.56 cm-1 and the Al−O vibration at 799.48 cm-1. The needle-like morphology of ZSM-23 was observed during SEM-EDS analysis. When calculated using BET analysis, the synthetic zeolite also exhibited a high surface area of 433.517 m2 g-1. Upon application in a batch experiment, the maximum adsorption capacity of the zeolite for amoxicillin (AMX) adsorption in aqueous solution was found to be 673.5 mg g-1. The adsorption data fitted the Langmuir isotherm better than the Freundlich one, with a correlation factor of 0.9328. This suggested the monolayer interaction, possibly between the negatively charged zeolite surface and the NH3+ group from AMX. However, the physical adsorption mechanism with the zeolite surface may also occur due to the high surface area. Considering the low production cost, this zeolite offers high economic value as an alternative sorbent for removing antibiotics in water effluent.